TiVo-lution. - Barton, Jim (New York ACM, 2006)
The challenges of delivering a reliable, easy-to-use DVR service to the masses
Keywords: Information systems; Information interfaces and presentation; Multimedia information systems; Video (e.g. tape, disk, DVI).; Information storage and retrieval; On-line information services; Web-based services; Information interfaces and presentation; Computing Milieux; Personal computing; Application packages